Developing Infographics of Cakeapp Based Teaching Speaking Ideas for English Teacher in 10th Grade Odd Semester at SMK Negeri 2 Singaraja - Gunawan, I Wayan (Journal of Educational Study, 2024)
This study aims to develop infographics of learning ideas to improve speaking skills through CakeApp at SMKN 2 Singaraja. The method used in this study is ADDE, with the subjects of the study being English teachers of grade 10. The data in this study were obtained through document analysis, observation, and interviews which were then processed using quantitative and qualitative methods. The results of the study indicate that computer-based learning media are still rarely used and require teaching innovation. The results of the study showed that the infographics developed obtained a score of 90-93% with a very good category from experts regarding content and products. This study is expected to provide innovation for computer-based speaking skills learning for students in the tourism industry.